2017
DOI: 10.1007/s11356-017-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of selected elements (Ti, Sr, Ba, V, Ga, Sn, Tl, and Sb) in deposited dust and human hair samples: implications for human health in Pakistan

Abstract: The current study determined, for the first time, the levels of titanium (Ti), strontium (Sr), barium (Ba), vanadium (V), gallium (Ga), tin (Sn), thallium (Tl), and antinomy (Sb), in deposited dust, and human hair collected from general population of different geographical areas of Pakistan. All the samples were prepared by microwave digestion and measured by ICP-MS. The results showed that on deposited dust samples, the detected elements followed the descending trend as: Ti > Sr > Ba > V > Ga > Sn > Tl > Sb s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…In the recent global collective against environmental pollution, road dust and roadside soil have been useful indicators of metals pollution in metropolitan cities and urban areas (Ferreira-Baptista and De-Miguel 2005;Shi et al 2008;Johansson et al 2009;Li et al 2016;Chang et al 2009;Benhaddya et al 2016;Eqani et al 2018). The metals occur naturally in the earth's crust, but as a result of anthropogenic activities, their natural levels have exceeded over many years of development in cities and urban areas (Malkoc et al 2010).…”
mentioning
confidence: 99%
“…In the recent global collective against environmental pollution, road dust and roadside soil have been useful indicators of metals pollution in metropolitan cities and urban areas (Ferreira-Baptista and De-Miguel 2005;Shi et al 2008;Johansson et al 2009;Li et al 2016;Chang et al 2009;Benhaddya et al 2016;Eqani et al 2018). The metals occur naturally in the earth's crust, but as a result of anthropogenic activities, their natural levels have exceeded over many years of development in cities and urban areas (Malkoc et al 2010).…”
mentioning
confidence: 99%
“…Also, studies have identified that the human colostrum and breast milk generally contained less than 1.0 ng/g of vanadium of dry weight [143]. Additionally, vanadium concentrations in scalp hair of healthy adults have been found in the range of 433 pg/g to 90 ng/g [144][145][146][147]. In general, the evidence has demonstrated that the most tissues contain less than 10 ng vanadium/g wet weight.…”
Section: Vanadium Tissue Distribution From Humans and Animal Studiesmentioning
confidence: 99%
“…Moreover, some authors reported the contamination of the vicinity by radionuclides and other rare elements as a consequence of the waste from the tin industry smokestacks 6,44 . Some recently published studies on dust were not suitable for comparison as they did not assess tin concentration or disregarded indoor domestic dust 45,46 .…”
Section: Environmental Samplesmentioning
confidence: 99%